Handwritten character recognition and prediction of age, gender and handedness using machine learning - Al Emran, Md.; Naief, S. M.; Hossain, Md. Shimul (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.